105 Altering the time of vaccination against respiratory pathogens enhanced antibody response and health of feedlot cattle. (29th July 2019) - Schubach, Kelsey; Cooke, Reinaldo F; Brandão, Alice; Schumaher, Thiago; Souza, Osvaldo; Bohnert, David; Marques, Rodrigo
Abstract: Angus × Hereford calves (n = 159; 87 heifers and 72 steers) were ranked by sex, body weight (BW), and age, and assigned to 1 of 3 vaccination schemes against the bovine respiratory disease (BRD) complex: 1) vaccination at weaning (d 0) and booster at feedyard entry (d 30; CON, n = 53), 2) vaccination 15 d before weaning (d -15) and booster 15 d before feedyard entry (d 15; EARLY, n = 53), and 3) vaccination 15 d after weaning (d 15) and booster 15 d after feedyard entry (d 45; DELAYED, n = 53). Calves were maintained on pasture from d -15 to 30, transported (d 30) for 480 km to a commercial growing yard, and moved (d 180) to an adjacent finishing lot where they remained until slaughter (d 306). Calves were assessed for BRD signs daily from d 0 to 306 according to the DART system. Blood samples were collected and BW recorded on d -15, 0, 15, 30, 45, 60, 75, and 180. Hot carcass weight was recorded upon slaughter, and carcass quality assessed after a 24-h chill. No treatment effects were detected (P ≥ 0.49) for BW gain and carcass traits (P ≥ 0.32). Incidence of BRD (d 0 to 306) was lessened (P < 0.01) in EARLY vs. CON and DELAYED, and similar (P = 0.17) between CON and DELAYED. Treatment × day interactions were detected (P ≤ 0.02) for serum antibody titers against bovine herpesvirus-1, bovine viral diarrhea virus-1, parainfluenza3, and bovine respiratory syncytial virus, which were greater (P ≤ 0.05) in EARLY vs. CON and DELAYED upon feedyard entry. Hence, anticipating initial and booster vaccination against respiratory pathogens to provide both doses prior to shipping appears to be a valid strategy to enhance cattle health responses and mitigate BRD in feedyards.